A Fun Palace: A Mixed Reality Event Through the Looking Glass of Cybernetics - Pennefather, Patrick; Rizzotti, Patrick; Desnoyers-Stewart, John; Stepanova, Katerina; Riecke, Bernhard; Danenkov, Leonid; Ryzhov, Vladislav; Saroyan, Julie-anne; Beltran, William; Chak, Riya (Cybernetics and Human Knowing, 2020)
This article depicts a reimagining of the Fun Palace (Littlewood, Price, Pask and others, 1960s) as a mixed reality event through the eyes of a newbie to the field of cybernetics. The Fun Palace thrived on having multiple definitions. It was an idealized, utilitarian, educational, anything-goes, communal, co-constructed participant-citizen playground existing within an architectural design that resisted a singular definition. Of particular relevance to our mixed-reality event, was the idea of the Fun Palace as an adaptive ecosystem dependent on context, time and the needs of those who would occupy it. The one-day mixed reality event was produced with this in mind. Our version of a fun palace took place in a 10,000 square foot hanger at the Centre for Digital Media in Vancouver, Canada on June 25th, 2019. The event consisted of several interactive installations inspired by some elements of cybernetics across a variety of disciplines and historical time periods. This article delicately proposes an examination of several of the installations that made up the Fun Palace: Carnival of Mixed Reality, through the polysemic lens of cybernetics.
Keywords: NSERC DG 2026; Riecke; Riecke_2020; bernhard-riecke; john-desnoyers-stewart; journalPaper; katerina-stepanova; patrick-pennefather; patrick-rizzotti; thesis-related